2019
DOI: 10.1136/bmjopen-2019-029582
|View full text |Cite
|
Sign up to set email alerts
|

From EHR to PHR: let’s get the record straight

Abstract: This article reflects on the changing nature of health information access and the transition of focus from electronic health records (EHRs) to personal health records (PHRs) along with the challenges and need for alignment of national initiatives for EHR and PHR in the National Health Service (NHS) of the UK. The importance of implementing integrated EHRs as a route to enhance the quality of health delivery has been increasingly understood. EHRs, however, carry several limitations that include major fragmentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…40 Many documents also described eHealth systems as a means to improve access and exchange of information and data (n=57/86, s=144). [41][42][43][44][45][46] Over half of the documents also reported that eHealth would improve the quality of care (n=48/86, s=107) 47 , and support research and policy (n=43/86, s=92). Other perceived benefits included patient empowerment & engagement, 46,[48][49][50][51] improvements to patient safety and data security 53 , reduction of costs, better service monitoring 54 and generally increased ability to address challenges that emerge.…”
Section: Benefits Of Ehealth Systemsmentioning
confidence: 99%
“…40 Many documents also described eHealth systems as a means to improve access and exchange of information and data (n=57/86, s=144). [41][42][43][44][45][46] Over half of the documents also reported that eHealth would improve the quality of care (n=48/86, s=107) 47 , and support research and policy (n=43/86, s=92). Other perceived benefits included patient empowerment & engagement, 46,[48][49][50][51] improvements to patient safety and data security 53 , reduction of costs, better service monitoring 54 and generally increased ability to address challenges that emerge.…”
Section: Benefits Of Ehealth Systemsmentioning
confidence: 99%
“…Currently, many governments view integrated or unified ePHR as a promising tool to improve the quality of healthcare (Fragidis and Chatzoglou, 2018; Kasteren et al, 2017; Symons et al, 2019) because of the various potential benefits for all parties involved, especially clinicians, healthcare managers and healthcare consumers (Detmer et al, 2008; Tang et al, 2006). Anticipated benefits include easy and timely access to patient information, enhancement of workflow flexibility and reliability and increased productivity (Detmer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Hospitals having better quality of care were more interested in adopting IT [20]. Many countries have keenly watched the progress of their PHR systems and those of other nations [21][22][23]. There are many barriers and facilitators associated with PHR adoption and use, and those barriers usually are related to technological, organizational, financial, and legal issues [24].…”
mentioning
confidence: 99%